Sizing of an autonomous microgrid considering droop control. (March 2022) - Rey, Juan M.; Jiménez-Vargas, Iván; Vergara, Pedro P.; Osma-Pinto, Germán; Solano, Javier
Highlights: An evaluation of the impact of droop control design on autonomous MGs sizing costs is presented. A case study of a solar/wind/battery/diesel microgrid is formulated and modelled. A comparison of costs between an hourly optimized EM used as a benchmark and multiple droop control scenarios is performed. A generalizable design methodology to calculate droop parameters is presented. Abstract: Autonomous microgrids are a suitable solution for off-grid electrification in terms of costs and reliability. The correct sizing of its generation and storage systems ensures efficient utilization of the available energy resources. Generally, many sizing approaches assume optimized energy management strategies that rely on central control architectures. However, these architectures are not always available, especially in limited investment microgrid projects. For this reason, the study of operation scenarios based on decentralized control strategy such as droop control is relevant. Based on this, this paper aims to evaluate the impact of the droop control over the sizing results of a solar/wind/battery/diesel microgrid. For this purpose, a case study of a sizing problem is presented, including the formulation and modelling. Results are presented comparing an hourly optimized energy management scenario with multiple values of the droop control parameters. Simulations results indicate that a competitive total cost can be obtained if the droop parameters are calculated considering the microgrid sizing results. Based on this, a generalizable design methodology for this purpose is presented.